Public accountability reform in a Nigerian ministry. Issue 4 (8th October 2018) - Sulu-Gambari, Waziri; Stafford, Anne; Stapleton, Pamela
Abstract : Purpose: This paper aims to address the gap within the public accountability literature with regard to emerging economies and add to knowledge about how accountability is understood and how it plays out in practice in the context of public sector reform. While prior literature has focussed on the resource dependence of emerging nations, this paper examines the practice of public accountability in a non-resource-dependent emerging economy. Design/methodology/approach: In a non-resource-dependent nation, we used a framework based on institutional theory but also draw upon the notion that international financial institutions act in an imperialist way to maintain their relationship with the country. The paper develops a concept of subtle coercion to explain the findings in relation to public accountability reform. The paper examines three reforms introduced and partially implemented in Nigeria: a local initiative that fits well with local understandings of what public accountability is and two imported initiatives that rely upon Western notions of accountability. The research method is a qualitative case study. Findings: The paper reveals the ways in which accountability reform is complex and subtle. Local understanding of what accountability is led to perceptions that a locally designed reform had enjoyed some success, even though by its own admission Nigeria's public sector still has a long distance to travel in terms of international notions of public accountability. Research limitations/implications: The research is based in a single country which allows for in-depth study but limits the ability to generalise findings. Originality/value: This case shows that specific and dynamic features of the political and economic environment can influence the nature of public accountability reform in a way which is not predictable or linear.